Pharmacological blockade of muscle afferents and perception of effort: a systematic review with meta-analysis - Bergevin, M.; Steele, J.; Payen de la Garanderie, M.; Feral-Basin, C.; Marcora, S. M.; Rainville, P.; Caron, J. G.; Pageaux, B. (Sports Medicine, 2023)
Background: The perception of effort provides information on task difficulty and influences physical exercise regulation and human behavior. This perception differs from other-exercise related perceptions such as pain. There is no consensus on the role of group III/IV muscle afferents as a signal processed by the brain to generate the perception of effort. Objective: The aim of this meta-analysis was to investigate the effect of pharmacologically blocking muscle afferents on the perception of effort. Methods: Six databases were searched to identify studies measuring the ratings of perceived effort during physical exercise, with and without pharmacological blockade of muscle afferents. Articles were coded based on the operational measurement used to distinguish studies in which perception of effort was assessed specifically (effort dissociated) or as a composite experience including other exercise-related perceptions (effort not dissociated). Articles that did not provide enough information for coding were assigned to the unclear group. Results: The effort dissociated group (n = 6) demonstrated a slight increase in ratings of perceived effort with reduced muscle afferent feedback (standard mean change raw, 0.39; 95% confidence interval 0.13-0.64). The group effort not dissociated (n = 2) did not reveal conclusive results (standard mean change raw, - 0.29; 95% confidence interval - 2.39 to 1.8). The group unclear (n = 8) revealed a slight ratings of perceived effort decrease with reduced muscle afferent feedback (standard mean change raw, - 0.27; 95% confidence interval - 0.50 to - 0.04). Conclusions: The heterogeneity in results between groups reveals that the inclusion of perceptions other than effort in its rating influences the ratings of perceived effort reported by the participants. The absence of decreased ratings of perceived effort in the effort dissociated group suggests that muscle afferent feedback is not a sensory signal for the perception of effort.